Gênero e economia solidária: um olhar sobre a participação e atuação das mulheres nas organizações do Terceiro Setor - Herk, Andréa Costa Van (2011)
There are several cuttings of everyday life that, force the women to assume different roles, trying to juggle family and profissional life. Even with the growth of the feminine participation in any kind of job market the several responsibilities assumed day by day still provide series of inequalities in the gender relations. Into opportunities in the ambit of the organizations of social economy aimed at production and commercialization of goods and/or community servies, possibly ruled in solidarity and cooperation, the women involved in these initiatives seem to be able to minimize some of these inequalities. This dissertation tried to open in a wide way, a discussion with the aim of analyzing how are the relations arising from the participation and role of women in the management of social economy organizations. This, due to the amount of institutions with the possibility of study that include feminine participation, thus, chose to study gender relations in management of two organizations of social economy in the city of Uberlândia, Minas Gerais. Thus, the empirical study sought to consider some categories of analysis - complicity, resistance and confrontation - from Medeiros (2008), and in the everyday relations in the social economy organizations, checking his influence on the dimensions of social management - social , economic, ecological and organizational and technical - Andion (2005). To develop the theoretical outline, this study is pointing out subjects to make possible understanding addressing the entangled interaction among the terms, gender, Third Section, social economy, social management and conflicts. Gender was addressed not only being limited to the male/female, but, seeking in several contexts that made possible to glimpse inequalities, such as, formation, social class, raça/etnia, among others. The Third Sector was contextualized, tapering concepts and derivations of the phenomenon of social economy, in the scene of composing the scenery of the possible opportunities to mitigate gender differences. They were considered, also, several perspectives, making a counterpoint and searching analysis of the social management in the organizations of social economy that has been studied. In this context, subjects were approached about organizacionais conflicts in the Third Section institutions, making situations that hinder, or even impede the growth of those organizations. The methodological procedures used in the investigation outline an interpretative technical approach, since the analysis techniques completed the way of the study of cases. The technique of the direct observation was used in the field research, since the data collection was composed by documental analysis, individual narratives and in group of the subjects in the management positions, being supplemented with individual interviews, in order to compose the triangulation of data. The survey results showed that the initiatives of solidarity economy organizations studied before are noteworthy and recognition, not only in civil society but also in the ambit of State, for fighting effectively for transforming critical local realities. However, the social administration is surrounded of several lacks, and the problems are magnified by conflicts in social relations, influenced by gender categorizations which affected the development of social economy organizations.